2015
DOI: 10.1021/ma502133f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic/Hydrophilic Triblock Copolymers: Synthesis and Properties of Physically Cross-Linked Hydrogels

Abstract: Hydrophobic/hydrophilic triblock copolymers of poly-(2-(N-ethylperfluorooctanesulfonamido)ethylmethyl acrylate) and poly(N,N′-dimethylacrylamide) (PD) were synthesized by sequential reversible addition−fragmentation chain transfer polymerization. Physically cross-linked hydrogels were produced by immersing compression-molded triblock copolymers into water. The copolymers and their hydrogels were characterized by differential scanning calorimetry, thermogravimetric analysis, thermal desorption-GC/MS analysis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…Polymer cross-linking may be reversible or irreversible depending upon the nature of the cross-linking. Three main types of cross-linking methods are widely studied [24][25][26]. These cross-linking methods are chemical, physical, and biological [27].…”
Section: Cross-linked Polymersmentioning
confidence: 99%
“…Polymer cross-linking may be reversible or irreversible depending upon the nature of the cross-linking. Three main types of cross-linking methods are widely studied [24][25][26]. These cross-linking methods are chemical, physical, and biological [27].…”
Section: Cross-linked Polymersmentioning
confidence: 99%
“…Noncovalent interactions enable autonomous self‐healing, including hydrogen bonding, hydrophobic bonding, host–guest interaction, and electrostatic ionic force . Chen et al .…”
Section: Properties Of Cphsmentioning
confidence: 99%
“…Noncovalent interactions enable autonomous self-healing, including hydrogen bonding, hydrophobic bonding, host-guest interaction, and electrostatic ionic force. 51,59,60 Chen et al introduced multiple hydrogen-bonding 2-ureido-4[1H]pyrimidinone (UPy) groups as crosslinking points into PAni/ PSS network to form self-healing hydrogel. 61 Dynamic reversibility of hydrogen bonds is beneficial to energy dissipation and network reconstruction, which is the fundamental mechanism of self-healing properties of hydrogels fracture surface at room temperature and show 3600% of the original extensibility.…”
Section: Self-healing Propertiesmentioning
confidence: 99%
“…Sui et al 35 reported rapid responsive thickening and self-assembly of a brush copolymer viz., poly(ethylene oxide)-gra-poly(N,Ndimethylaminoethyl methacrylate) in aqueous solution. Many hydrophobically modied polymers when dissolved in water at concentrations in the semidilute unentangled regime in the presence or absence of surfactants show gelation either at room temperature [36][37][38][39][40][41][42][43][44][45][46][47][48][49] or upon increasing temperature. 50 In comparison, the examples of polymer solutions that gel upon cooling are fewer.…”
Section: Introductionmentioning
confidence: 99%